Indigenous Writings from the Convent : Negotiating Ethnic Autonomy in Colonial Mexico - Díaz, Mónica, 1974- (Book collections on Project MUSE., 2010)
Indigenous Writings from the Convent examines ways in which indigenous women participated in one of the most prominent institutions in colonial times--the Catholic Church--and what they made of their experience with convent life. This book will appeal to scholars of literary criticism, women's studies, and colonial history, and to anyone interested in the ways that class, race, and gender intersected in the colonial world. --Book Jacket.